Graph Drawing 18th International Symposium, GD 2010, Konstanz, Germany, September 21-24, 2010. Revised Selected Papers - Brandes, Ulrik; Cornelsen, Sabine; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2011)
This volume constitutes the refereed proceedings of the 18th International Symposium on Graph Drawing, GD 2010, held in Konstanz, Germany, during September 2010. The 30 revised full papers presented together with 5 revised short and 8 poster papers were carefully reviewed and selected from 77 submissions. The volume also contains a detailed report about the 17th Annual Graph Drawing Contest, held as a satellite event of GD 2010. Devoted both to theoretical advances as well as to implemented solutions, the papers are concerned with the geometric representation of graphs and networks and are motivated by those applications where it is crucial to visualize structural information as graphs.
Keywords: Computer science—Mathematics.; Algorithms; Computers; User interfaces (Computer systems).; Discrete Mathematics in Computer Science; Math Applications in Computer Science; Algorithm Analysis and Problem Complexity; Models and Principles; Symbolic and Algebraic Manipulation; User Interfaces and Human Computer Interaction